Addition to the checklist of IUCN European wild bees (Hymenoptera: Apoidea). Issue 1 (2nd January 2017) - Rasmont, Pierre; Devalez, Jelle; Pauly, Alain; Michez, Denis; Radchenko, Vladimir G.
Summary: The present study is an update to the first Red List of European Bees published in 2014. The additional records are based on (i) comprehensive review of literature; (ii) new data provided by bee specialists in response to the publication of the first Red List; (iii) new developments in taxonomy of European bees including description of new cryptic species; (iv) new specimens from recent field collections. While the first Red List included a list of 1965 wild bee species with 75 genera, we found 86 additional species, while two more genera have been erected ( Seladonia and Vestitohalictus ), giving an updated total of 2051 species and 77 genera. The authors discuss the artificial framework of the study considered by International Union for Conservation of Nature (IUCN) to produce the first Red List and they propose the more meaningful West Palaearctic biogeographical region. For this whole region, a first estimation gives 3408 wild bee species in 105 genera. The next taxa have been erected from subspecies to species status: Andrena ( Euandrena ) limosa Warncke, 1969, stat. n ., Andrena ( Plastandrena ) oligotricha Mavromoustakis, 1952, stat. n .